2007
DOI: 10.1111/j.1557-9263.2007.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal nest predation: a potential obstacle to recovery of a Florida Scrub-Jay population

Abstract: Population declines among birds are often linked to habitat change and associated increases in nest predation rates. In species of conservation concern identifying nest predators is an important first step in developing management strategies to mitigate low nesting success caused by depredation. Because predator composition varies geographically and with landscape factors habitat restoration may need to be tailored to reduce locally important predators. We used miniature video cameras to identify nest predator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…Despite the high risk of nocturnal predation (Isbell 1990;Stake and Cimprich 2003;Carter et al 2007;Reidy et al 2009), animals must find a balance between vigilance and sleep (Lima et al 2005) and this balance is likely to affect their antipredator behavior. During sleep, animals can still be responsive to potential dangers but this depends on their sleep state and the type of danger (Velluti 1997;Coenen and Drinkenburg 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the high risk of nocturnal predation (Isbell 1990;Stake and Cimprich 2003;Carter et al 2007;Reidy et al 2009), animals must find a balance between vigilance and sleep (Lima et al 2005) and this balance is likely to affect their antipredator behavior. During sleep, animals can still be responsive to potential dangers but this depends on their sleep state and the type of danger (Velluti 1997;Coenen and Drinkenburg 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal reports indicate that diurnal primates and birds sometimes emit vocalizations in response to nocturnal threats but do not seem to mob the predators (Vessey 1973;Busse 1980; reviewed by Southern et al 1982;Shealer and Kress 1991;Carter et al 2007). For example, ring-billed gulls emitted alarm calls when they were disturbed at night and fled from the area (Emlen et al 1966;Southern et al 1982).…”
Section: Introductionmentioning
confidence: 96%
“…The only comparable studies of European woodland songbirds reported either predominantly (Schaefer 2004) or exclusively (Stevens et al 2008) diurnal predation, as most nests in these studies were depredated by Jays. Distinctly different diel patterns were reported from other systems with different principal predators: mainly nocturnal predation by carnivores on wader nests in grasslands (MacDonald and Bolton 2008;Teunissen et al 2008) and Skylark Alauda arvensis nests in arable fields (Morris and Gilroy 2008), mainly nocturnal predation by snakes (Carter et al 2007) or mainly diurnal predation by sciurid rodents and raptors (Liebezeit and George 2002) on arboreal nests. The all-day predation by mammals was not only due to the occurrence of both nocturnal and diurnal species.…”
Section: Diel Activity Of Nest Predatorsmentioning
confidence: 90%
“…These rare vocalizations may be ineffective at repelling intruders or attracting mates. A more parsimonious explanation for these rare nocturnal vocalizations may be an individual's reaction to a disturbance event, such as nest predation (as seen in some species; jays, Aphelocoma coerulescens: Carter, Legare, Breininger, & Oddy, 2007;peahens, Pavo cristatus: Yorzinski & Platt, 2012) or environmental factors, such as moonlight (York, Young, & Radford, 2014). However, recent work has demonstrated seasonal variation in the occurrence of nocturnal songs in the field sparrow, Spizella pusilla, a species that rarely sings at night (Celis-Murillo, Stodola, Pappadopoli, Burton, & Ward, 2016), potentially indicating a role of nocturnal singing in reproductive activities.…”
mentioning
confidence: 99%